THE IMPACT OF PROVINCIAL MINIMUM WAGE INCREASES AND ECONOMIC GROWTH RATES ON POVERTY LEVELS IN DKI JAKARTA - Sutrisno Sutrisno (Jurnal Ekonomi, 2022)
This study aims to determine the effect of the provincial minimum wage variables and the rate of economic growth on the poverty level. This study uses quantitative time series data (years 2010-2021) in DKI Jakarta Province. Based on multiple linear regression analysis, the partial test showed that the increase in the UMP had no significant effect on the poverty level in DKI Jakarta. In contrast, the economic growth rate significantly affected the poverty level in DKI Jakarta. Simultaneous testing shows that the increase in the UMP and the rate of economic growth have a simultaneous and significant effect on the poverty level in DKI Jakarta. The results of the Coefficient of Determination test, the increase in the UMP, and the economic growth rate contributed 75.9% to the poverty rate, and other variables outside this study influenced the remaining 24.1%.